Le Corbusier e Parigi - Bartocci, Gabriele (Firenze Architettura, 2021)
Some unpublished watercolours from 1908, exhibited for the first time at the Teatro dell'Architettura in Mendrisio on the occasion of the exhibition dedicated to the early drawings of a young Le Corbusier, constitute the documentary corpus that has made it possible to identify the matrix of the plans of some projects for Paris, particularly of the Plan Voisin, which the architect designed in 1925.